Differential associations between sensory loss and neuropsychiatric symptoms in adults with and without a neurocognitive disorder. (20th July 2017) - Kiely, Kim M.; Mortby, Moyra E.; Anstey, Kaarin J.
ABSTRACT: Background: To investigate the differential associations between sensory loss and neuropsychiatric symptoms among older adults with and without diagnosed neurocognitive disorder. Methods: The sample comprised 1, 393 adults (52.3% men) aged between 72 and 79 years from a community-based cohort study. There were 213 cases of mild and 64 cases of major neurocognitive disorders. The main outcome was number of informant reported symptoms on the Neuropsychiatric Inventory (NPI). Sensory loss was defined by visual acuity worse the 0.3 logMAR (6/12 or 20/40) and self-reported hearing problems. Results: Clinically relevant NPI symptoms were reported in 182 (13.1%) participants, but no individual symptom occurred in more than 5% of the total sample. Among participants diagnosed with a major neurocognitive disorder, those with any sensory loss had over three times (95%CI: 1.72–11.78) greater rates of NPI symptoms than those with unimpaired levels of sensory functioning. There were no differences in the number of neuropsychiatric symptoms by type of sensory loss, and no additional risk associated with a dual sensory loss compared to a single sensory loss. There was no evidence of an association between sensory loss and number of neuropsychiatric symptoms among cognitively healthy adults. Conclusions: The extent to which this association is the result of underlying neuropathology, unmet need, or interpersonal factors is unclear. These findings have significant implications for dementia care settings, including hospitals and respite care, as patients with sensory loss are at increased risk of neuropsychiatric symptoms and may require additional psychosocial support. Interventions to manage sensory loss and reduce the impact of sensory limitations on neuropsychiatric symptoms are needed.